Doing the right thing approximately not the wrong thing precisely : challenges of monitoring impacts of pro-poor interventions in tourism value chains - Ashley, Caroline (Overseas Development Institute LondonGB, 2008)
Provides some guidance on key questions to address in measuring the impact of value chain interventions and the extent to which information needs differ for diagnostics, baselines and monitoring.